PENGARUH BAHAN TAMBAH KIMIA TERHADAP MUTU KUAT LENTUR BETON - Yamali, Fakhrul Rozi; Fakhrul Rozi Yamali (Jurnal Ilmiah Universitas Batanghari Jambi, 2011)
Compressive strength of concrete states the quality of a structure. Flexural compressive strength is related to the bending of a beam element as a result of the transverse load. Flexural compressive strength test was conducted at the Laboratory of the Faculty of Engineering University of Batanghari. The test method is to use two of loading points such that the third of the middle stretch of only receiving bending moment. The use of chemical additive, Sikament-NN, varying aims to see its influence on the resulting flexural strength.Results showed that the addition of Sikament-NN variation 0.5%, 1% and 1.5%, is obtained that the addition of Sikament-NN by 1% to the value of compressive strength and flexural strength are optimal. Keywords: concrete, strong, pliable material added.